Metodología analítica para estimar los gases de efecto invernadero (GEI) producidos a partir de los generadores de vapor OTSG en las operaciones de campos de crudo pesado. (2023)
This degree work focuses its efforts on analyzing from an explanatory research methodology, taking as theoretical foundations the branches of thermodynamics and chemical reactions, to determine from mathematical analysis, the implications of greenhouse gases and so on. same the quality of the water vapor obtained by the combustion of natural gas from an OTSG steam generator.